A, The Pengembangan Eletronik Lembar Kerja Peserta Didik (E-LKPD) Berbasis Pendekatan Kontekstual Meenggunakan Live Worksheets Materi Teks Deskripsi Siswa Kelas VII Sekolah Menengah Pertama Negeri 1 Bintan Tahun Pelajaran 2023/2024: Pengembangan Eletronik Lembar Kerja Peserta Didik (E-LKPD) Berbasis Pendekatan Kontekstual Meenggunakan Live Worksheets Materi Teks Deskripsi Siswa Kelas VII Sekolah Menengah Pertama Negeri 1 Bintan Tahun Pelajaran 2023/2024 - Neni Jumaidah, Neni Jumaidah; Harry Andheska; Siti Habiba (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to development E-LKPD Based on a Contextual Approach Using Live Worksheets for Text Description Material for Grade VII SMP Students by measuring the level of validity and practicality of the E-LKPD being developed. The development model used in this research is the 4D model which starts from the define, design, develop stages. E-LKPD was validated by three experts, namely material experts, language experts and product experts. The data analysis techniques in this research are quantitative descriptive to analyze product validity and practicality assessment scores and qualitative descriptive to analyze comments, suggestions and input on the product. The results of this research are (E-LKPD) Based on a Contextual Approach Using Live Worksheets with a percentage of validation from material experts reaching 89% with the qualification